Aplicativo direcionado para engenharia de agrimensura: e topo - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The present work of completion of course was based on developing a compact tool where you can group some calculations pertinent to Surveying Engineering (mainly the transformation of coordinates and reference systems), using Google's virtual application development platform for Android, maintained by the Massachusetts Institute of Technology (MIT), where it is possible to develop free APK applications using block programming, make applications easy to install on smartphones and tablets with the Android Operating System. The lack of tools for the exchange of information between geodesy, cartography and topography are important problems for the good management of projects and works, and, in the absence of these resources, are implemented incorrectly. Although they exist, the proprietary softwares are scarce in the market and do not cover all the necessary solutions, especially the transition of coordinates of a cartographic projection plane in coordinates in the local topographic plane, necessary for the materialization of a project without the risk of errors generated by the negligence of the effects of the terrestrial curvature. The simplification of these calculations by means of a mobile application is of paramount importance to the professionals of the area, not only of Surveyor Engineer, but of all the professionals that use coordinate systems in their works and they need to carry out the conversion of these coordinates in diverse systems according to the need, facilitating the learning process, especially for students who need an efficient and instant conference of their work, done in the classroom and / or in the field.
Keywords: Aplicativo; Cartografia; Coordenadas; Geodésia; Topografia; Application; Cartography; Coordinates; Geodesy; Topography; CNPQ::ENGENHARIAS